Benefits of a right anterolateral minithoracotomy rather than a median sternotomy in isolated tricuspid redo procedures - Maimaiti, Aikebaier; Wei, Lai; Yang, Ye; Liu, Huan; Wang, Chunsheng (Journal of Thoracic Disease; Vol 9, No 5 (May 28, 2017): Journal of Thoracic Disease, 2017)
Background: To compare results of tricuspid valve (TV) reoperation between incision via a right anterolateral minithoracotomy (RAMT) and median sternotomy (MS). Methods: We performed a retrospective analysis of 49 patients who underwent isolated TV surgery as a reoperation at our institution between 2006 and 2015. Previous cardiac operations included mitral, aortic, and TV surgeries, atrial septal defect repair, and pericardiectomy. The mean age of the patients was 51.9±12.8 years, 14 (28%) were male and 35 (72%) were female. Follow-up was 95% (38/40) complete, with a mean duration of 41.3±19.5 months. Results: Perioperative demographic and laboratory tests did not show any significant differences between the RAMT and MS groups. The drainage volume, total red cell unit, total serum volume and platelet were significantly different 1150±803.5/2,270±1,920, 4.8±4.1/8.7±8.9, 478.2±488.9/950.0±857.6, 0.04±0.21/0.38±0.64 (P